Unusual Oral Manifestations of autoimmune disorders - Saumya Khare (Journal of Orofacial Research, 2023)
Autoimmune diseases (ADs) impact oral health, both directly and indirectly. Immune-related disorders of the oral cavity may occur as primary disease process, secondary to systemic disease or neoplasm, or as a reaction to medications and other agents. The entities represented within this group may vary significantly by severity, clinical presentation, microscopic presentation, and special testing results. Increasing evidence is emerging for a steady rise of autoimmune diseases in the last decades. The oral physician can therefore play a pivotal role in the detection and during the following multidisciplinary treatment. Precise and early diagnosis increases the efficiency and efficacy of the treatment strategy. Therefore, the goal of our manual is to present the most “uncommon” autoimmune diseases that may show the first oral clinical signs and symptoms which are a manifestation of the general clinical disease.